Improving Plant Growth and Alleviating Photosynthetic Inhibition and Oxidative Stress From Low-Light Stress With Exogenous GR24 in Tomato (Solanum lycopersicum L.) Seedlings - Lu, Tao; Yu, Hongjun; Li, Qiang; Chai, Lin; Jiang, Weijie (Frontiers in Plant Science, 2019)
Low light (LL) is one of the main limiting factors that negatively affect tomato growth and yield. Techniques of chemical regulation are effective horticultural methods to improve stress resistance. Strigolactones (SLs), newly discovered phytohormones, are considered as important regulators of physiological responses. We investigated the effects of foliage spray of GR24, a synthesized SLs, on tomato seedlings grown under LL stress conditions. The results showed that application of GR24 effectively mitigated the inhibition of plant growth and increased the fresh and dry weight of tomato plants under LL. Additionally, GR24 also increased the chlorophyll content (Chla and Chlb), the net photosynthetic rate (Pn), the photochemical efficiency of photosystem (PS) II (Fv/Fm), and the effective quantum yield of PSII and I [Y(II) and Y(I)], but decreased the excitation pressure of PSII (1-qP), the non-regulatory quantum yield of energy dissipation [Y(NO)] and the donor side limitation of PSI [Y(ND)] under LL. Moreover, application of GR24 to LL-stressed tomato leaves increased the electron transport rate of PSII and PSI [ETR(II) and ETR(I)], the ratio of the quantum yield of cyclic electron flow (CEF) to Y(II) [Y(CEF)/Y(II)], the oxidized plastoquinone (PQ) pool size and the non-photochemical quenching (NPQ). Besides, GR24 application increased the activity and gene expression of antioxidant enzymes, but it reduced malonaldehyde (MDA) and hydrogen peroxide (H2O2) content in LL-stressed plants. These results suggest that exogenous application of GR24 enhances plant tolerance to LL by promoting plant utilization of light energy to alleviate the photosystem injuries induced by excess light energy and ROS, and enhancing photosynthesis efficiency to improve plant growth.